2019
DOI: 10.18699/vj19.525
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome studies of origin, selection and adaptation of the Russian cattle breeds

Abstract: Our review presents several recent studies on the genetic history and signatures of selection in genomes of the native Russian cattle breeds. Most of these works are not easily accessible for the Russian-speaking audience. We describe the origins of appearance of the Russian cattle breeds from the genetics perspective. We point to the links between most of the Russian breeds with the taurine breeds of the European origin and for some Russian breeds with the breeds of the Asian origin. We describe major phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Cluster analysis revealed that the Black Pied and Holstein (HOL) populations were distributed between two different clusters (see Table 3), which confirms their genetic affinity (Yurchenko et al, 2018;Yudin, Larkin, 2019). The similar ity coefficient values for all the populations except D turned out to be much lower than that of HOL, which evidences different HOL pedigree levels in the investigated Black Pied populations (Zinovieva et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
“…Cluster analysis revealed that the Black Pied and Holstein (HOL) populations were distributed between two different clusters (see Table 3), which confirms their genetic affinity (Yurchenko et al, 2018;Yudin, Larkin, 2019). The similar ity coefficient values for all the populations except D turned out to be much lower than that of HOL, which evidences different HOL pedigree levels in the investigated Black Pied populations (Zinovieva et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
“…In this regard, attention is paid to increasing the number of Kalmyk cattle. Along with traditional methods of breeding, they began to use an assessment based on the breeding value index (Yudin and Larkin, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of SNPs allow the detection selection signatures, such as specific shift in the frequency alleles and haplotypes frequency, as well as an increase or reduction in genetic diversity. This helps to identify modifications in the cattle genome in response to natural and artificial selection, and also loci and genetic variants directly affecting traits important for adaptation and production [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%